Manufacturing processes for engineered cement-based composite material products - De Koker, Don; Van Zijl, Gideon Pieter Adriaan Greeff (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng)--University of Stellenbosch, 2004.